A review of the pollen analysis of South Asian honey to identify the bee floras of the region. (2nd January 2016) - Jamil Noor, Mehwish; Ahmad, Mushtaq; Ashraf, Muhammad Aqeel; Zafar, Muhammad; Sultana, Shazia
Abstract : This review focuses on previous work on honey pollen analysis (melissopalynology) to determine the bee floras of South Asian honeys. After a brief historical introduction on melissopalynology, the abundance and distribution of pollen and the nectar source for bees of specific regions are identified. With the help of 124 research papers referenced, a list of the bee flora of South Asia has been compiled, representing 750 plants serving as the pollen sources. Knowledge of bee floras of this region will prove to be significant for beekeepers during nomadic beekeeping, by increasing pollination and honey production and, hence, improving the apiculture industry of the region.